Learning problems reported by college students: are they using learning strategies? - Rachal KC; Daigle S; Rachal WS (Journal of Instructional Psychology, 2007)
As teachers of higher education, we expect students to enter college with some understanding of what it means to be an effective learner and the ability to apply effective learning strategies. Unfortunately, many students do not develop effective learning strategies unless they receive explicit instruction and the opportunity to apply these skills. The current study focused on identifying students' self-reported problems engaging in several academic tasks. We hypothesized that students would report less learning difficulties as they matriculated through the curriculum. This study also identified which learning difficulties are most prevalent at according to student self-reports. Student behaviors related to studying and learning strategies were assessed with an on-line version of the Learning Needs Questionnaire. Factor analysis identified fourteen factors related to academic learning needs. Regardless of academic classification, students reported learning problems related to poor information processing, reading, writing, motivation to study, math, and test taking skills. Test anxiety was the only factor that demonstrated a significant difference between academic classifications. Recommendations are made to improve student use of learning strategies across the curriculum.